Performance of some potato accessions of USA and Bangladesh in relation to dry matter yield and biochemical constituent (Journal of the Bangladesh Agricultural University, 2016)
Present research was designed to evaluate the dry matter yield and biochemical constituents of twenty two potato accession of USA in comparison with two Bangladeshi varieties. Studied biochemical constituents were starch, protein and vitamin C contents. Analyses were performed from November 2014 to April 2015 in different laboratories of Bangladesh Agricultural University, Mymensingh. Potato accessions differed significantly with respect to dry matter content and biochemical parameters. Dry mater content was found highest in accession AC 10110. Considering biochemical constituent, the accession AC 10062 showed highest protein and vitamin C contents. On the other hand, accession AC 10081 had the highest starch content. Significant positive correlation was observed between dry matter and starch content while significant negative correlation was observed between starch and protein contents. Considering both dry matter yield and biochemical parameters AC 10081 was found as the best USA potato accession for cultivation in Bangladesh.J. Bangladesh Agril. Univ. 13(2): 215-220, December 2015